842. Impact of Active Treatment of Carbapenem-Resistant Acinetobacter baumannii Infections in US Hospitals Between 2014 and 2019. (31st December 2020) - Pogue, Jason M; Zhou, Yun; Kanakamedala, Hemanth; Cai, Bin
Abstract: Background: Treatment choices for carbapenem-resistant (CR) Acinetobacter baumannii infections are limited. We analyzed the impact of active treatment on outcomes in patients infected with CR vs carbapenem-susceptible (CS) A. baumannii . Methods: Adult patients hospitalized between January 1, 2014 and June 30, 2019 with A. baumannii infections recorded in the Premier Database were retrospectively evaluated. Outcomes including mortality, discharge status (home vs other), and readmission rates were calculated as a function of receipt of active antibiotic treatment, infection site, and CR status. Antibiotic therapy was considered active if given after the index culture and displaying in vitro susceptibility. Results: Among 3, 500 patients with A. baumannii (CR n=1, 608; CS n=1, 892), 2, 057 patients (58.8%) received active treatment, with a much lower proportion of CR A. baumannii patients receiving active treatment than CS patients (606 [37.7%] vs 1, 451 [76.7%]). Patients without active treatment had similar rates of in-hospital mortality (14.3% vs 12.9%, P =0.25) but were less likely to be discharged to home (26.3% vs 37.0%, P < 0.001) than those that received active treatment. No association between receipt of active treatment and overall mortality or discharged status was demonstrated for CR isolates (Table 1). However, among the subset of patients with CR bloodstream infections, mortality was higher in those without active treatment compared to those with active treatment (55.1% vs 25.9%, P =0.009). Overall readmission rates due to A. baumannii were considerably higher for those who did not receive active treatment vs those who did (16.0% vs 7.5%, P < 0.001) and the same was seen by differing infection sites; primarily driven by CR patients with bloodstream, respiratory, or urine infections (Table 2). Table 1. Mortality and discharge status by active treatment and carbapenem susceptibility Table 2. Readmission due to A. baumannii by active treatment and CR status among patients discharged alive Conclusion: Active antibiotic therapy was associated with improved outcomes in patients with A. baumannii infections, although perhaps not to the extent expected. Further investigation into the impact of active therapy on outcomes is warranted. Disclosures: Jason M Pogue, PharmD, BCPS, BCIDP, Shionogi Inc. (Advisor or Review Panel member) Yun Zhou, MS, Shionogi Inc. (Independent Contractor) Hemanth Kanakamedala, BS, Shionogi Inc. (Independent Contractor) Bin Cai, MD, PhD, Shionogi Inc. (Employee)